Black Well-Being : Health and Selfhood in Antebellum Black Literature - Stone, Andrea, 1971- (Book collections on Project MUSE., 2016)
By analyzing slave narratives, emigration polemics, and black-authored fiction pieces, Stone reveals many reflections of injury, illness, disease, and disability, but she also highlights the equally numerous emphases on well-being by black authors.